STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN KAWASAN WISATA MUARA KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA TAHUN 2015 - Benni Olan Hutapea; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Based on the Medium Term Development Plan of North Tapanuli Regency Year 2014-2019, established Vision makes North Tapanuli as a tourist destination, one of which is the development of tourist areas Muara. In its development until 2015, several programs and activities in realizing the North Tapanuli as a tourist destination especially Muara travel area development can not be realized with the maximum. The purpose of this study to determine the strategy of local governments in the development of the tourist area of Muara 2015 and the factors that affect the implementation of tourism development Muara 2015. The research was qualitative descriptive research data collection is by interview and documentation, or the document search , The theory used in this research is the theory of government management, strategy theory and the theory of the development of tourism. From the results of the field studies showed that some programs and activities in the development of the tourist area of Muara not running maximum, there's even a program that does not bejalan due to lack of budget or funds obtained by the Department of Tourism and Culture of North Tapanuli. The factors that affect the implementation of tourism development Muara based on theory and management strategies of government, namely: lack of awareness, lack of funds, lack of human resources, and the lack of supporting facilities. The local government should conduct an evaluation of the programs can not be implemented so that the next policy can be more effective. Keywords: Tourism Development, Development strategy, management of the Government.